Coal Ball Seed CBS: Ekonomi Sirkular Limbah Batu Bara Dalam Resolusi Reklamasi Lahan Pasca Tambang: Coal Ball Seed CBS: Circular Economy of Coal Waste in Post-Mining Land Reclamation Resolution - Wardana, Wisnu; Dira, Dira; Dewi, Nabila Aulia; Pambuko, Ari Galih; Siaahan, Reynal Ricardo; Nugraha, Nanda Satya; Putra, Dian Pratama; Suparyanto, Teddy (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
Indonesia is one of the world's largest producers and exporters of coal. Approximately 60 percent of Indonesia's total coal reserves consist of low-quality coal, which is cheaper and has a calorific value of less than 6,100 kcal/gram. In addition to the combustion of low-quality coal waste, there are also Fly Ash and Bottom Ash (FABA). The circular economy has become an important part of the economic model approach, aiming to drive economic growth while minimizing social and environmental damage. Innovations related to coal waste utilization and post-mining reclamation solutions are key aspects of this approach. This study aims to utilize coal waste as a medium for land reclamation using the circular economy concept. Coal Ball Seed (CBS) is an innovation that packages coal into balls containing seeds, growing media, and nutrients, providing the necessary nourishment for seed growth. The best binder found in this study was soil. Coefficient tests showed that the significance level for the composition was below the 0.05 threshold. The test results indicated aSig. value of 0.00, confirming that Coal Ball Seed (CBS) significantly affects the growth of sengon seeds (Falcataria moluccana. The R-square summary test revealed a value of 38.1%, meaning that the growth of Falcataria moluccana seeds is influenced by the composition of CBS itself, while the remaining 61.9% is influenced by other factors. Thus, the optimal CBS composition uses a ratio of Bottom Ash: Clay: Antracol: Liquid Nutrient. The average nutrient content of CBS was measured at N 9 mg/kg, P 2.6 mg/kg, and K 4.3 mg/kg. The utilization of coal waste into CBS plays a role in the circular economy, and its spherical shape makes it highly feasible for distribution via drones in large-scale reclamation efforts